Directed assembly of a high surface area 2D metal–organic framework displaying the augmented "kagomé dual" (kgd-a) layered topology with high H2 and CO2 uptake. Issue 5 (20th February 2017) - Spanopoulos, Ioannis; Tsangarakis, Constantinos; Barnett, Sarah; Nowell, Harriot; Klontzas, Emmanuel; Froudakis, George E.; Trikalitis, Pantelis N.
Abstract : A high surface area layered MOF withkgd-a topology, based on a nanosized and highly aromatic hexagonal linker, shows high H2 and CO2 uptake. Abstract : The rigid and highly aromatic hexatopic, carboxylate-based organic linker H6 L, under solvothermal reaction conditions with CoCl2 ·6H2 O, directs the assembly of two new 2D MOFs (denoted as1 and2 ) with the rarekgd-a layered topology, as revealed by single crystal X-ray diffraction measurements. A unique 3-connected dinuclear cluster, Co2 (–COO)3 Cl, was observed in1 and this MOF was found to be stable upon solvent removal, in contrast to2, where single Co 2+ cations serve as 3-c nodes and the structure collapses upon activation. A detailed Ar sorption measurement at 87 K revealed that1 has an apparent BET surface area of 1299 m 2 g −1 with narrow pore size distribution, centered at 6.9 Å. A very high H2 and CO2 uptake is observed reaching 209.9 cm 3 (STP) g −1 and 106.8 cm 3 (STP) g −1 at 77 K/1 bar and 273 K/1 bar, respectively, which is attributed to the combination of small pore size and the high density of aromatic rings in1 .